The Use of Cinchona Alkaloid Derivatives as Chiral Ligands and Organocatalysts in Asymmetric Catalysis - Li, Minghua; He, Wei; Zhang, Sheng-Yong (Mini-Reviews in Organic Chemistry, 2022)
Cinchona alkaloids are natural products extracted from cinchona plants, which contain quinine, quinidine, cinchonine, and cinchonidine. During the past 30 years, due to their attractive structural properties, these compounds have been used as chiral skeletons and organocatalysts in asymmetric organic synthesis. In this review, we summarize the applications of cinchona alkaloids derivatives in asymmetric catalysis recently developed by our group, including oxidation, reduction, and C-C bonds formation. These studies have solved some of the problems with the various asymmetric reactions discussed, while also enriching alkaloids chemistry, providing new ideas for the design and synthesis of chiral catalysts, and providing abundant experimental data for the chiral induction process.
Keywords: oxidation